Fun Arabic Learning through Songs Media - Hanifah, Umi (Tanwir Arabiyyah: Arabic as Foreign Language Journal, 2021)
In this study, the authors focused on learning Arabic through songs media. The research method in this study is descriptive using a qualitative approach. Through studies from various sources in the form of books, journals, research reports, and the phenomenon of Arabic learning in Indonesia, the author describes how the concept of songs as a medium of Arabic learning and how the implementation of songs media in Arabic learning as an effort to improve the quality of Arabic learning. The conclusion of this study is that the song is an appropriate medium of Arabic learning in arousing students' interest and motivation to learn. The use of songs media in Arabic learning can create an atmosphere of learning that is relaxed, fun and exciting, so students do not feel bored and fed up in following the learning process in class. The selection of songs that suits students' emotional and intellectual needs and the teacher's skills in practicing the technique of using song media in Arabic learning is the main key to the success of a learning that uses songs as a instructional medium.